FPGA-based Digital Baseband Transmission System Performance Tester Research and Design - Huimin Duan; Juanjuan Gu; Guohua Hu; Qian Zhang (Universitas Ahmad Dahlan, 2017)
Communication System Transmission Performance Tester, as a digital communication system design and testing equipment, plays an important role in the construction and daily maintenance of the communication system. The paper presents a kind of tester, which is designed using Cyclone IV FPGA (Field Programmable Gata Array) and VHDL (Very High Speed Integrated Circuits Hardware Description Language). According to the features in the eye diagram, the system performance can intuitively and qualitatively evaluated. The results prove that the system accurately displayed the eye diagram, thereby reflected the performance of the baseband transmission system truthfully